"Participating means accepting": debating and contesting synthetic biology. Issue 2 (3rd April 2017) - Meyer, Morgan
Abstract : This article analyses opposition to public debates. In doing so, the article builds upon the tradition of analyzing controversies by symmetrically describing the advocates and the opponents of public debates. First, the public debates on synthetic biology will be placed in their wider political and institutional context. The call for a "serene" debate by the French public authorities will be retraced and its genealogy vis-à-vis previous controversies (i.e. on genetically modified organisms (GMOs) and nanotechnology) will be elucidated. The article then describes how the group Pièces et main d'œuvre (PMO) obstructed a public debate on synthetic biology, an obstruction that will be analyzed by mobilizing and extending the notion of divisible versus indivisible conflicts. But the article will also move beyond the symmetrical analysis of a controversy by discussing one of the criticisms raised by PMO, that some researchers are "sociologists of acceptability." The notions of divisibility, indivisibility and what I call "inversibility" will be used to reflect upon the positionality of social scientists and to offer a constructive view for a sociology of acceptability.